The Effect of Mechanical Gymnastic Mushroom on Learning Circle in Artistic Gymnastics for the Young - Mohameed, Salma; Samir, Luma (Journal of Physical Education, 2021)
The research aimed at identifying the differences between pre and post-test in controlling and experimental groups as well as identifying the differences between both groups in posttests of circle skill and identifying the rule of the mushroom in learning the skill understudy. The researchers used the experimental method on (8) gymnasts aged (6 – 8) years old from Baghdad/ AL Rusafa divided into two equal groups. The researchers designed and made mechanical mushroom to teach circle skill in artistic gymnastics. The results showed that the mechanical mushroom has a significant effect on earning circle skill in artistic gymnastics.